2020
DOI: 10.3389/fpsyg.2020.00797
|View full text |Cite
|
Sign up to set email alerts
|

Gender Effects in Observation of Robotic and Humanoid Actions

Abstract: Robots are gaining an increasingly important role in industrial production. Notably, a high level of acceptance is an important factor for co-working situation between human and robot. The aim of the present study was to investigate the differences in the perception of anthropomorphic and robotic movements using models consisting of a virtual robot and a digital human. Videos of each model displayed different degrees of human likeness or robot likeness in speed and trajectories of placing movements. Female and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 29 publications
(31 reference statements)
1
26
0
Order By: Relevance
“…On the one hand, there is some evidence in the present findings for transfer of social behaviors from human-human to human-AI interaction, supporting predictions made by the CASA framework (Nass et al, 1994;Nass et al, 1997). For example, female shadowers align toward human and voice-AI model talkers to the same degree, in line with findings by Abel et al (2020) who found that female participants showed no difference in perception of human-likeness for movements produced by a virtual robot and a digital human. However, in the same study, males did show a distinction (rating the digital human movements as more humanlike than the robot).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the one hand, there is some evidence in the present findings for transfer of social behaviors from human-human to human-AI interaction, supporting predictions made by the CASA framework (Nass et al, 1994;Nass et al, 1997). For example, female shadowers align toward human and voice-AI model talkers to the same degree, in line with findings by Abel et al (2020) who found that female participants showed no difference in perception of human-likeness for movements produced by a virtual robot and a digital human. However, in the same study, males did show a distinction (rating the digital human movements as more humanlike than the robot).…”
Section: Discussionsupporting
confidence: 90%
“…Understanding differences in how females and males communicate with voice-AI can reflect how speech patterns are transferred from human-human communication to linguistic interactions with technological agents. Indeed, there is much interest in understanding the role of gender in behavioral patterns during human-computer interaction (e.g., Abel et al, 2020). Recent work has begun to explore gender-differences in attitudes and perceptions toward technological agents and, in particular, during human-robot interaction (see Nomura (2017) for survey).…”
Section: Gender and Technologymentioning
confidence: 99%
“…Third, females might prefer the high-agency female assistant, because it is the one, they would most readily identify with. In past studies, women were found to have a stronger tendency to anthropomorphize machines (e.g., Abel et al, 2020 ) and to identify with fictional screen characters than men ( Aytulun and Sunai, 2020 ). Women who view themselves as independent and assertive might therefore prefer to identify with an artificially intelligent counterpart that corresponds to a more contemporary image of women.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging data were collected from the same group of participants as in the study by Abel et al (2020). A total of 40 right-handed healthy volunteers, with twenty male and .…”
Section: Participantsmentioning
confidence: 99%